Aggregate uncertainty, HANK, and the ZLB - Alessandro Lin; Marcel Peruffo (European Central Bank (ECB), 2024)
We propose a novel methodology for solving Heterogeneous Agents New Keynesian (HANK) models with aggregate uncertainty and the Zero Lower Bound (ZLB) on nominal interest rates. Our efficient solution strategy combines the sequence-state Jacobian methodology in Auclert et al. (2021) with a tractable structure for aggregate uncertainty by means of a two-regimes shock structure. We apply the method to a simple HANK model to show that: 1) in the presence of aggregate non-linearities such as the ZLB, a dichotomy emerges between the aggregate impulse responses under aggregate uncertainty against the deterministic case; 2) aggregate uncertainty amplifies downturns at the ZLB, and household heterogeneity increases the strength of this amplification; 3) the effects of forward guidance are stronger when there is aggregate uncertainty.
Keywords: D14; E44; E52; E58; 330; Monetary Policy; New-Keynesian Models; Liquidity Traps; Zero Lower Bound; Computational Methods